2021
DOI: 10.1590/1414-431x2021e11679
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to varenicline protects against locomotor alteration in a MPTP mouse model of Parkinson's disease

Abstract: The beneficial effects of drugs that act via nicotinic acetylcholine receptors (nAChRs) on Parkinson's disease (PD) symptomatology may explain the negative correlation between cigarette smoking and risk of this neurological condition. Varenicline, an α4β2 nAChR partial agonist approved for smoking cessation treatments, could be valuable for PD treatment. Here, we investigated varenicline effects in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) PD mouse model. From postnatal day (PN) 90 to PN119, male C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…33 The administration of MPTP has been reported to induce locomotor problems in PD animals. 34 In the previous investigation, the results demonstrated that MPTP-treated animals exhibited motor function impairments as compared to the naïve control animals. Of note, these deficits improved upon PB treatment seven days after MPTP injection.…”
Section: Discussionmentioning
confidence: 89%
“…33 The administration of MPTP has been reported to induce locomotor problems in PD animals. 34 In the previous investigation, the results demonstrated that MPTP-treated animals exhibited motor function impairments as compared to the naïve control animals. Of note, these deficits improved upon PB treatment seven days after MPTP injection.…”
Section: Discussionmentioning
confidence: 89%
“…The test was performed according to previous studies [ 11 , 13 , 14 , [17] , [18] , [19] , [20] , [21] ]. The mice were forced to swim for 6 min in a cylindrical vessel with 30 cm height and 10 cm diameter, filled with water at 24 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The test was conducted in a white closed box (40 x 40 × 40 cm). The test was performed according to previous studies [ 11 , 12 , 18 , 19 , 22 , 23 ]. Mice were gently placed in the center of the box and freely explored.…”
Section: Methodsmentioning
confidence: 99%
“…The test was performed according to previous studies [11,[13][14][15][16][17][18][19]. The mice were forced to swim for 6 min in a cylindrical vessel with 30 cm height and 10 cm diameter, filled with water at 24 .…”
Section: Forced Swim Testmentioning
confidence: 99%
“…The test was conducted in a white closed box (40 x 40 x 40 cm). The test was performed according to previous studies [11,12,16,17,20,21]. Mice were gently placed in the center of the box and freely explored.…”
Section: Open Field Testmentioning
confidence: 99%